Effect of oral L-Glutamine supplementation on Covid-19 treatment (2020)
Objectives: The aim of this study is to investigate the effect of oral L-Glutamine supplementation on hospitalization time, need for intensive care unit and Coronavirus Disease-19 (Covid-19) mortality. Methods: The study included 30 Covid-19 patients using L-Glutamine and 30 Covid-19 patients who did not use L-Glutamine with similar age, gender and clinical status. Diagnostic tests, laboratory examinations, clinical findings and computed thorax tomography imaging of the patients were evaluated. Results: Hospitalization time was 10.4 ± 1.9 days in Covid-19 without L-Glutamine group and 8.9 ± 1.8 days in Covid-19 with LGlutamine group (p ¼ 0.005). In Covid-19 without the L-Glutamine group, four patients require the ICU though no one in the other group required that (p ¼ 0.038). Only one mortality was observed in Covid-19 without the L-Glutamine group (p ¼ 0.999). Conclusions: Nutritional supplements such as L-Glutamine boost immune system especially by inhibition of inflammatory responses. Our results suggest adding enteral L-glutamine to the normal nutrition in the early period of Covid-19 infection may lead to a shortened hospital stay and lead to less need for ICU. Largerscale studies are needed to evaluate the effect of adding enteral LGlutamine to the currently used treatments in the infectious diseases especially like Covid-19.